Analisis Penggunaan Rem Magnetik Dengan Animasi Sederhana - Ghayrie Habsy Alghifary; Rahmad Fauzi (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
This article discusses the use of Faraday’s law and Lorenz's force in the use of magnetic brake technology on motorbikes in an effort to increase the efficiency and sustainability of transportation. The magnetic brake is made of non-ferromagnetic metal, the disk is flanked by a coil that carries an electric current which is then regulated by a driver and uses an Arduino to be able to regulate and measure the current strength in the magnetic brake. The research results show that magnetic brakes are able to provide significant speed reduction by producing consistent and responsive braking force. With the wider use of magnetic brakes, these findings show the great potential of magnetic brake technology in improving the operational efficiency of motorbikes. Research supports further development and application of this technology in the automotive industry.